Perbedaan Kadar Zink ASI pada Ibu Postpartum dengan Anemia dan Tidak Anemia - Rini Mustikasari Kurnia Pratama (Poltekkes Kemenkes Maluku, 2021)
Zinc is one of the substances needed in breast milk for baby growth. Zinc deficiency is a common health problem that affects the development of children and contributes to diseases such as diarrhea, pneumonia, and malaria. The purpose of this study was to determine the difference in zinc levels in the first week postpartum mothers with anemia compared to postpartum mothers who were not anemic. The research design used observational analytic with a cross-sectional approach, with purposive sampling. Examination of zinc levels in breast milk using spectrophotometry. Data analysis used an unpaired t-test. The test results obtained that the average zinc level in the first week postpartum mothers who were not anemic was 0.40±0.350 mg/L while the average zinc level in the first week postpartum mothers with anemia was 0.42±0.439 mg/L with p-value=0.92 (p>0.05). There was no difference between zinc levels in the first week postpartum mothers with anemia and not anemia. The zinc concentration in breast milk is highest during colostrum, while the lowest value is between 7-12 months of lactation and increases during weaning.